Answer:
12:3
Step-by-step explanation:
Answer: 53 degree
Explanation:
AEB + BEC + CED = 180 degree
37 + 90 + CED = 180
CED = 180 - 127
CED = 53 degree
Answer:
60 degrees
Step-by-step explanation:
The angles all have to add up to 180, so you can do
![34 + 86 +x = 180\\120 + x = 180\\x = 60](https://tex.z-dn.net/?f=34%20%2B%2086%20%2Bx%20%3D%20180%5C%5C120%20%2B%20x%20%3D%20180%5C%5Cx%20%3D%2060)
First multiply 60 x 6 x 45 = 16,200
Then divide, 16,200/350=46.2857
Answer:
(a) h^-1(x) = (x+6)/6
Step-by-step explanation:
The inverse relation can be found by solving for y: x = h(y).
<h3>Solution</h3>
x = h(y) . . . . . the inverse relation
x = 6y -6 . . . . . use the function definition
x +6 = 6y . . . . add 6
(x +6)/6 = y . . . . divide by 6
The inverse function is ...
![\boxed{h^{-1}(x)=\dfrac{x+6}{6}}](https://tex.z-dn.net/?f=%5Cboxed%7Bh%5E%7B-1%7D%28x%29%3D%5Cdfrac%7Bx%2B6%7D%7B6%7D%7D)